Homotopic functional connectivity disruptions in glioma patients are associated with tumor malignancy and overall survival. Issue 1 (30th November 2021) - Daniel, Andy G S; Hacker, Carl D; Lee, John J; Dierker, Donna; Humphries, Joseph B; Shimony, Joshua S; Leuthardt, Eric C
Abstract: Background: Gliomas exhibit widespread bilateral functional connectivity (FC) alterations that may be associated with tumor grade. Limited studies have examined the connection-level mechanisms responsible for these effects. Given the typically strong FC observed between mirroring/homotopic brain regions in healthy subjects, we hypothesized that homotopic connectivity (HC) is altered in low-grade and high-grade glioma patients and the extent of disruption is associated with tumor grade and predictive of overall survival (OS) in a cohort of de novo high-grade glioma (World Health Organization [WHO] grade 4) patients. Methods: We used a mirrored FC-derived cortical parcellation to extract blood-oxygen-level-dependent (BOLD) signals and to quantify FC differences between homotopic pairs in normal-appearing brain in a retrospective cohort of glioma patients and healthy controls. Results: Fifty-nine glioma patients (WHO grade 2, n = 9; grade 4 = 50; mean age, 57.5 years) and 30 healthy subjects (mean age, 65.9 years) were analyzed. High-grade glioma patients showed lower HC compared with low-grade glioma patients and healthy controls across several cortical locations and resting-state networks. Connectivity disruptions were also strongly correlated with hemodynamic lags between homotopic regions. Finally, in high-grade glioma patients with known survival times ( n = 42), HC in somatomotor and dorsal attention networks were significantly correlated with OS. Conclusions: These findings demonstrate an association between tumor grade and HC alterations that may underlie global FC changes and provide prognostic information.